How is Software Engineering Linked to Business? A Scopus-Based Bibliometric and Visualization - Almagribi, Ahmad Bilal; Ardianto, Fikky; Taufan, Anas; Kristomo, Domy (AI Society & STMIK Indonesia, 2025)
Software engineering has significantly impacted various fields, including business, yet there had been no comprehensive bibliometric analysis of its interaction with business until this study. This research filled the gap by examining key contributors, affiliations, countries, and leading journals using a bibliometric analysis of 100 Scopus-indexed documents. The study revealed a peak in publications in 2008 with 11 documents, highlighting Gruhn, V. from Universität Leipzig, Germany, as the most prolific author. Both Germany and the United States were prominent, contributing 21 documents each.